PKM Produksi Kascing Oleh Masyarakat Tani di Desa Barang Kabupaten Soppeng - Amirah Mustarin; Lahming Lahming; Indrayani Indrayani; Nur Rahmah; Asrijal Asrijal (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
PKM for vermicompost farming communities in Barang Village, Liliriaja District, Soppeng Regency is a new technology and innovation implemented to overcome waste problems. The farmer group involved is Wanita Tani Melati, which is a group of oyster mushroom cultivators. One of the organic wastes that has not been processed by the community is baglog waste from oyster mushroom cultivation. The technology introduced to the local community is the use of baglog waste from oyster mushroom cultivation as a medium for cultivating worms Lumbricus rubellus where the results of the metabolism of the worms become vermicompost which is better than ordinary compost which can be directly applied to plants. This PKM was carried out in 2 stages, namely the training stage which lasted 1 day and the vermicompost production stage using baglog waste media and Lumbricus rubellus worms and assistance for 4 months. From this PKM activity, 200 kg of vermicompost was successfully produced in a period of 2 months. It is hoped that making vermicompost independently can be a solution for farmers so that they do not depend on synthetic fertilizers purchased or subsidized by the government and can also increase income for oyster mushroom farmers from the sale of vermicompost and worms.